Classroom Assessment Perceptions among EFL Students: An Analysis Using the Student Perception Assessment Questionnaire (SPAQ) - Wagiyo, Supiah; Putri, Diyola Rahmadona (EEdJ: English Education Journal, 2025)
This study explored students' perceptions of classroom assessment using the Student Perception Assessment Questionnaire (SPAQ) among English Language Education Department (TBI) students at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. The research aimed to examine differences in perception across semesters II, IV, VI, and VIII, and to identify assessment methods used by lecturers. Data collected through questionnaires were analyzed quantitatively, with SPAQ showing high reliability (Cronbach alpha = 0.908). Results showed that students' perceptions were generally high, with the highest mean found among sixth-semester students, suggesting that maturity and study duration influence perceptions. The Authenticity dimension received the highest score, indicating that students view assessments as relevant to real-life contexts. Lecturers primarily employed authentic assessments, including performance, portfolio, and self-assessment methods. Statistical analysis (ANOVA) revealed no significant differences in perception scores across semesters, F (3, 38.724) = 0.159, p = .923. It is recommended that future research incorporate psychological factors, learning maturity, environmental influences, and academic achievement to further understand student perceptions of classroom assessment.